Hepatobiliary manifestations in patients with ulcerative colitis: a retrospective analysis - Stratmann, Katharina; Aydolmus, Songül; Gu, Wenyi; Heling, Dominik; Spengler, Ulrich; Terjung, Birgit; Strassburg, Christian P.; Vollenberg, Richard; Blumenstein, Irina; Trebicka, Jonel (Frontiers in Medicine, 2024)
Background Inflammatory bowel diseases (IBDs) are often associated with altered liver function tests (LFTs). There is little data on the relationship between abnormal LFT and IBD. Our study aimed to evaluate the prevalence and etiology of elevated LFT in patients with ulcerative colitis (UC) and to determine whether there is an association with clinical and demographic parameters. Methods The clinical records of the Gastroenterology Outpatients Clinic at a single center were reviewed and screened for patients with UC from 2005 to 2014. In total, 263 patients were included. Patients with Crohn’s disease (CD), colitis indeterminate, and colitis of other origins were excluded. Abnormal LFT and liver injuries were analyzed. Results A cohort of 182 patients was analyzed (114 males, 68 females; mean age = 50.2 ± 16.1 years). 58 patients had already been diagnosed with a hepatobiliary disorder. Patients with a known hepatobiliary disorder suffered from UC for a significantly longer duration. Elevated LFT in patients without known hepatobiliary disorders was 69.4%. Liver injury was found in 21.8%. A transient increase in abnormal LFT was shown in 59 patients (68.6%), a persistent increase was found in 27 patients (31.4%). Treatment with thiopurines was a risk factor for persistent elevated LFT (p = 0.029), steroids had a protective impact (p = 0.037). Conclusion This study clearly highlights the importance of screening for hepatobiliary disorders and abnormal LFT in patients with UC, as the prevalence of hepatobiliary disorders and abnormal LFT is detected very often among this patient group.